2021
DOI: 10.1038/s41419-021-04000-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR/Cas9 screening identifies CARHSP1 responsible for radiation resistance in glioblastoma

Abstract: Glioblastomas (GBM) is the most common primary malignant brain tumor, and radiotherapy plays a critical role in its therapeutic management. Unfortunately, the development of radioresistance is universal. Here, we identified calcium-regulated heat-stable protein 1 (CARHSP1) as a critical driver for radioresistance utilizing genome-wide CRISPR activation screening. This is a protein with a cold-shock domain (CSD)-containing that is highly similar to cold-shock proteins. CARHSP1 mRNA level was upregulated in irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Additionally, CARHSP1 was identified as a significant prognostic mRNA with the second-highest attention value. This result is also related to a recent study [ 54 ] that investigated whether CARHSP1 is radiotherapy protective in glioblastoma by signaling via the CARHSP1/TNF-α pathway. In addition, patients with high levels of CARHSP1 who are treated with radiotherapy have a poor prognosis.…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, CARHSP1 was identified as a significant prognostic mRNA with the second-highest attention value. This result is also related to a recent study [ 54 ] that investigated whether CARHSP1 is radiotherapy protective in glioblastoma by signaling via the CARHSP1/TNF-α pathway. In addition, patients with high levels of CARHSP1 who are treated with radiotherapy have a poor prognosis.…”
Section: Discussionsupporting
confidence: 80%
“…They further show that pharmacological activation of STING enhances the effects of ionizing radiation in vivo and might be a promising approach to enhance radiotherapeutic response in patients suffering from HNSCC (summarized in Table 1 ). In an interesting study, Zhu et al performed genome-wide CRISPR activation screening and identified calcium-regulated heat-stable protein 1 (CARHSP1) as an essential element involved in radioresistance traits in human glioblastoma cells (summarized in Table 1 ) [ 42 ]. Because of its cold-shock domain, CARHSP1 has the capacity to bind to polypyrimidine regions of single-stranded RNA, single-stranded DNA, or double-stranded DNA [ 59 ].…”
Section: High-throughput Screening Methods To Study Radiosensitivity ...mentioning
confidence: 99%
“…Intriguingly, CARHSP1 enhances mRNA stability of tumor necrosis factor-alpha (TNF-α), a crucial pleiotropic cytokine and a critical inflammatory molecule [ 60 ]. With this information, Zhu et al showed that an elevated level of CARHSP1 is associated with radioresistance of glioblastoma cells via CARHSP1/TNF-α pathway signaling [ 42 ]. Cheng et al used an unbiased genome-wide CRISPR/Cas9 knockout strategy in A549 lung cancer cells and identified plakophilin 2 (PKP2) as a critical driver of radiation resistance in lung cancer cells [ 61 ].…”
Section: High-throughput Screening Methods To Study Radiosensitivity ...mentioning
confidence: 99%
“…The underlying mechanism and changes in genes related to radiosensitivity were investigated further based on the results of clinical trials using common chemotherapy drugs combined with radiotherapy on three different bladder cancer cell lines (5637, TCCSUP, and J82). Zhu et al used the CRISPR/Cas9 SAM human lentiviral library, which contains 70,290 unique sgRNA sequences targeting 23,430 human genes, to screen the target genes related to radiotherapy sensitivity in neuroblastoma ( 9 ). Lan et al also used the CRISPR/Cas9 library to screen genes related to radiotherapy sensitivity in pancreatic cancer ( 10 ).…”
Section: Methodsmentioning
confidence: 99%